Spiritual Intelligence (SI): A Quranic Approach - Bensaid, Benaouda; Machouche, Saleh (2011)
It was designed to define or “rate” the intelligence of humans based on their mental capacity. Despite the efforts made to produce global models of spiritual intelligence reflecting diverse beliefs, values and cultures, they fail to understand the depth of religious and cultural differences. The Quranic special insight into developing spiritual competencies makes this issue an extremely interesting and vitally critical topic in need of analysis. This paper sheds light on a number of issues on spiritual intelligence according to the Quran, and seeks to develop a competency-based criterion for it. What is meant by ‘spiritually intelligent’ and what does spiritual intelligence look like? What are the spiritual qualities and revealing indicators of spiritual intelligence? What are the fundamental goals, defining characteristics and structure of spiritual intelligence according to the Quran? What are the spiritual qualities and revealing indicators of spiritual intelligence? What controls the course of spiritual perfection? This paper attempts to define a number of major headings on spiritual intelligence according to the Quran, and seeks to develop a competency-based criterion for spiritual intelligence. This paper furthermore provides several illustrations that effectively highlight the Quranic perspective with regards to the understanding and consequent application of spiritual intelligence as found in the stories of Cain and Abel, Prophet Ibrahim and Prophet Joseph.